Multifunctional flexible Ag-MOFs@CMFP composite paper for fruit preservation and real-time wireless monitoring of fruit quality during storage and transportation. (30th November 2022) - Zhang, Yuancheng; Li, Hao; Yao, Yuan; Shen, Xi; Xu, Chuanhui; Fu, Lihua; Lin, Baofeng
Highlights: Tight binding of Ag-MOFs in flexible Ag-MOFs@CMFP to CMFP by a novel strategy. Ag-MOFs@CMFP exhibits good humidity response and excellent antimicrobial properties. Ag-MOFs@CMFP can effectively extend the shelf life of fruits and monitor its quality. Remote monitoring of fruits is achieved by signal transmission to mobile phones. Abstract: The global annual fruit and vegetable waste accounts for more than half of food waste, and the main cause of this waste is the deterioration of fruit and vegetable. In addition, fruit spoilage can produce foodborne illnesses and pose a public health threat. In order to guarantee the quality and safety of fruits in the fruit supply chain. We prepared multifunctional silver based metal–organic frameworks@carboxymethyl filter paper (Ag-MOFs@CMFP) composite paper by in situ synthesis. The composite paper used in fruit packaging can effectively slows down fruit deterioration. Besides, Ag-MOFs@CMFP composite paper can reflect the quality of the fruit by detecting changes in humidity, which has yet to be reported elsewhere. Significantly, transmitting the humidity response signal to the mobile phone can realize remote real-time wireless monitoring of fruit quality. This work may contribute to achieve the integration of real-time wireless monitoring, preservation and packaging for fruit-supply chain.